Creative use of LMS, wikis and mobile technologies for learning. Proceedings - Konovalova, Eeya; Tamistove, Ekaterina; Thorvaldsen, Steinar (Murmansk State Humanities University, 2011)
Proceedings of the International Arctic Workshop, Tromsø, May 19–20, 2011.